Modulation of Inflammatory Responses by Wnt/β-Catenin Signaling in Dendritic Cells: A Novel Immunotherapy Target for Autoimmunity and Cancer - Suryawanshi, Amol; Tadagavadi, Raghu K.; Swafford, Daniel; Manicassamy, Santhakumar (Frontiers in Immunology, 2016)
The Wnt/β-catenin pathway is an evolutionarily conserved signaling pathway critical for several biological processes. An aberrant Wnt/β-catenin signaling is linked to several human diseases. Emerging studies have highlighted the regulatory role of the Wnt/β-catenin signaling pathway in normal physiological processes of parenchymal and hematopoietic cells. Recent studies have shown that the activation of Wnt/β-catenin pathway in dendritic cells (DCs) play a critical role in mucosal tolerance and suppression of chronic auto-immune pathologies. Alternatively, tumors activate Wnt/β-catenin pathway in DCs to induce immune tolerance and thereby evade anti-tumor immunity through suppression of effector T cell responses and promotion of regulatory T cell responses. Here, we review our work and current understanding of how Wnt/β-catenin signaling in DCs shapes the immune response in cancer and autoimmunity and discuss how Wnt/β -catenin pathway can be targeted for successful therapeutic interventions in various human diseases.